PEMBERDAYAAN IBU RUMAH TANGGA DALAM MENINGKATKAN KESEHATAN KELUARGA MELALUI MAKANAN DAN MINUMAN YANG BERKHASIAT OBAT - Hanifah Ikhsani; Rina Novia Yanti; Eno Suwarno (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2021)
The purpose of this activity is to provide solutions by providing socialization about the types of medicinal plants that can be used as raw material for making medicinal foods and drinks, the characteristics of Moringa leaves as ingredients for making food, training in making medicinal foods and drinks. The method used is to provide counseling materials, practice making medicinal foods and drinks, providing assistance and evaluation of results. The results of this dedication show that there is an increase in partners' knowledge about the definition, types and benefits of medicinal plants as raw materials for making medicinal foods and drinks tofu to tofu is 27% to 100%, from not knowing to tofu by 33% to 100% and partners who already know the knowledge of medicinal plants by 40% to 100%. As well as Partners are able and skilled at making healthy food and drinks.